2023
DOI: 10.3390/children10050791
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Lung Clearance Index as a Useful Outcome Marker in the Follow-Up of Pediatric Patients with Non-Cystic Fibrosis Bronchiectasis?

Abstract: The forced expiratory volume in one second (FEV1) is regularly used for the follow-up of patients with non-cystic fibrosis bronchiectasis (nCF-BE). The lung clearance index (LCI), measured by the multiple breath washout test, has been recently proposed as a lung function measure and a potential tool more sensitive than the FEV1 measured by spirometry in assessing airway changes seen on imaging. While several data have been endorsed as a useful endpoint in clinical trials of patients with early or mild CF lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Alkoussa et al compared LCI and FEV1 in 20 children ages 5−18 years with primary ciliary dyskinesia (PCD) and other causes of non-CF bronchiectasis. 5 They found that while 90% of patients had normal FEV1, only 55% had a normal LCI. There was no significant association between LCI and spirometric parameters.…”
Section: Multiple Breath Washout (Mbw)mentioning
confidence: 96%
See 1 more Smart Citation
“…Alkoussa et al compared LCI and FEV1 in 20 children ages 5−18 years with primary ciliary dyskinesia (PCD) and other causes of non-CF bronchiectasis. 5 They found that while 90% of patients had normal FEV1, only 55% had a normal LCI. There was no significant association between LCI and spirometric parameters.…”
Section: Multiple Breath Washout (Mbw)mentioning
confidence: 96%
“…While MBW has been well studied in CF lung disease, less is known about its utility in other conditions. Alkoussa et al compared LCI and FEV1 in 20 children ages 5−18 years with primary ciliary dyskinesia (PCD) and other causes of non‐CF bronchiectasis 5 . They found that while 90% of patients had normal FEV1, only 55% had a normal LCI.…”
Section: Multiple Breath Washout (Mbw)mentioning
confidence: 99%